An integrated assessment of heat hazard, vulnerability, and accessibility to climate shelter networks for identifying urban adaptation priority areas in Andalusia (Spain) - Vargas Molina, Jesús; Sortino-Barrionuevo, Juan Francisco; Castro Noblejas, Hugo (Elsevier, 2026)
Climate change is intensifying the effects of extreme heat, particularly in urban environments, posing a risk to public health and disproportionately affecting vulnerable populations. Urban climate shelters have emerged as a short-term adaptation measure, yet their deployment is often based on existing infrastructure and does not systematically respond to spatial patterns of heat hazard or social vulnerability. This study develops an integrated framework to assess the accessibility of climate shelter networks while explicitly accounting for territorial variations in hazard and population vulnerability. The approach combines hazards and vulnerability indices with network-based accessibility analysis to identify priority areas for intervention and urban adaptation planning. Applied to Andalusia (southern Spain), a Mediterranean climate change hotspot, the results reveal significant spatial mismatches between heat hazard and access to climate shelters, highlighting areas of compounded vulnerability. Results show that more than 50% of the resident population in Andalusia live in high or very high priority areas, considering hazard, vulnerability, and accessibility to climate shelters. The study provides a transferable, equity-oriented methodology to support disaster risk reduction and climate adaptation strategies under increasing heat stress.
Keywords: Cambio climático - Andalucía; Urban climate shelter; Accessibility; Vulnerable population; Extreme heat; Urban short-term adaptation